2011
DOI: 10.15288/jsad.2011.72.864
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Step Program Attendance and Polysubstance Use: Interplay of Alcohol and Illicit Drug Use

Abstract: ABSTRACT. Objective:The primary aim of this study was to advance understanding of the effi cacy of 12-step programs by determining the temporal relationships between alcohol and illicit drug use among 12-step program affi liates. Method: A total of 253 early 12-step affi liates without extensive histories of Alcoholics Anonymous (AA) attendance were recruited from substance use treatment and community-based AA. A majority of the sample met criteria for a diagnosis of alcohol dependence, reported lifetime use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Over a third had "some" or "a lot" of concern about their drinker's prescription or non-prescription drug use. This is consistent with recent rates of substance use disorder comorbidity from the Al-Anon membership survey, and research regarding the increasing prevalence of comorbid alcohol and drug addictions in 12-step groups (Al-Anon, 2012; Tonigan & Beatty, 2011). Both men and women reported that their drinkers had problems in many domains, particularly in their relationships with the CO, the drinker's alcohol use, and the drinker's overall quality of life, again highlighting the escalating problems that often lead to Al-Anon attendance (Cutter & Cutter, 1987).…”
Section: Drinker Characteristicssupporting
confidence: 86%
“…Over a third had "some" or "a lot" of concern about their drinker's prescription or non-prescription drug use. This is consistent with recent rates of substance use disorder comorbidity from the Al-Anon membership survey, and research regarding the increasing prevalence of comorbid alcohol and drug addictions in 12-step groups (Al-Anon, 2012; Tonigan & Beatty, 2011). Both men and women reported that their drinkers had problems in many domains, particularly in their relationships with the CO, the drinker's alcohol use, and the drinker's overall quality of life, again highlighting the escalating problems that often lead to Al-Anon attendance (Cutter & Cutter, 1987).…”
Section: Drinker Characteristicssupporting
confidence: 86%
“…Thus, if from baseline to 3 months, a participant used cocaine more than any other illicit drug, cocaine use days were divided by the number of days in the measurement period to attain a measure of IDD for that participant (cf. Tonigan & Beatty, 2011). Measuring IDD in this way provides a conservative estimate of drug use days when a participant uses multiple drugs within one assessment period.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that long-term investigations into the benefits of 12-step programs are relatively rare, and a majority of studies are limited to 12-month follow-up. Recent work also suggests that sustained 12-step attendance may even serve to off-set relapse to illicit drug use once alcohol use has occurred (Tonigan & Beatty, 2011). Understandably, then, many studies have sought to identify the prescribed 12-step behaviors and practices that predict increased abstinence (e.g., Kelly & Moos, 2003; Pagano, Friend, Tonigan, & Stout, 2004; Tonigan & Rice, 2010), with equal attention directed to understanding why these 12-step practices predict improved functioning.…”
Section: Introductionmentioning
confidence: 99%
“…To control for prior learning effects when investigating change processes, the parent study excluded adults who had prior success at achieving abstinence (Tonigan and Beatty, 2011;Tonigan and Rice, 2010). Thus, participants were excluded from the study if they had already achieved alcohol abstinence for 12 months or longer or had attended AA for more than 4 months.…”
Section: Participantsmentioning
confidence: 99%
“…Sample characteristics are reported in Table 1. Additional information regarding this sample has been published elsewhere (Jenkins and Tonigan, 2010;Tonigan and Beatty, 2011;Tonigan and Rice, 2010).…”
Section: Participantsmentioning
confidence: 99%